Cultural adaptation framework of social interventions in mental health: Evidence-based case studies from low- and middle-income countries. (February 2020) - Fendt-Newlin, Meredith; Jagannathan, Aarti; Webber, Martin
Background: Evidence-based strategies for treating mental health conditions need to be scaled up to address the mental health treatment gap in low- and middle-income countries. Most medical and psychological interventions for the treatment of mental health conditions have been developed and evaluated in high-income countries. However, the imperative of scaling up such interventions potentially ignores local realities, and may also discredit or replace local frameworks for responding to distress. Aims: This article aims to develop a framework for the cultural adaptation of social interventions which are developed within, and draw upon, local contexts, to ensure they are acceptable, feasible and effective. Method: A case study approach is used to discuss the feasibility of developing and adapting psychosocial interventions which are embedded in local knowledge, values and practices. Results: The first case study introduces yoga as an alternative and/or complementary, and culturally relevant, approach for people experiencing mental health conditions in India. The second case study is a cross-cultural adaptation of a psychosocial intervention from the United Kingdom to fit the local idioms of distress and service context in Sierra Leone, as the country battled with the Ebola outbreak. We use these case studies to develop a Cultural Adaptation Framework, which recognises that people and their mental health are products of their culture and society, to inform the future development, adaptation and evaluation of sociocultural interventions for people experiencing mental health conditions in low- and middle-income countries. Conclusion: The Cultural Adaptation Framework can be used to ensure interventions are culturally relevant and responsive to local conditions prior to evaluating in experimental studies.